“Cartas para profesar novicias y para dar hábito a monjas”, two unknown minor prints - Sánchez Herrador, Miguel Ángel (Revista General de Información y Documentación, 2024)
The notarial protocols preserved in our provincial historical archives hide very varied and often unknown forms of typologies. This is the case of the "cartas de profesar novicias" and "para dar hábito a monjas", two types of prints that had not been studied. To carry out this work we have consulted a sample of more than 700 notarial protocols, as well as reviewed the Clergy collection of the Archivo Histórico Provincial de Córdoba, which allowed us to identify 37 editions and 85 copies, between 1592 and 1829. Next, we analyze the documents located from different points of view, bibliographic, archival and historical, and prepare a catalogue.
Keywords: Letters; letter for the profession of novices; letter for bestowal of the habit to nuns; booklet; archives; convent life